Biofilm modulation and demineralization reduction after treatment with a new toothpaste formulation containing fluoride, casein phosphopeptide-amorphous calcium phosphate, and sodium trimetaphosphate: In situ study - Gonçalves, Francyenne Maira Castro [UNESP]; de Almeida, Eduarda Martins Fontes Cantarella; Hannig, Christian; Quinteiro, Julia Paião [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Cannon, Mark Lloyd; Danelon, Marcelle [UNESP] (Elsevier, 2024)
Objective: This in situ study aimed to evaluate a new toothpaste formulation containing fluoride (F), casein phosphopeptide amorphous calcium phosphate (CPP-ACP) and sodium trimetaphosphate (TMP) on the process of dental demineralization and biofilm composition. Methods: This crossover double-blind study consisted of five phases, in which 10 volunteers wore intraoral appliances containing four bovine enamel specimens. The cariogenic challenge was performed using 30 % sucrose solution. Blocks were treated 3 ×/day with the following toothpastes: 1) Placebo (No F-TMP-CPP-ACP), 2) 1100 ppm F (1100F), 3) 1100F + 3 %TMP (1100F-TMP), 4) 1100F + 10 %CPP-ACP (1100F-CPP-ACP) and 5) 1100F-CPP-ACP-TMP. After 7 days, the percentage loss of surface hardness (%SH), integrated loss of subsurface hardness (ΔKHN), F, calcium (Ca) and phosphorus (P) concentration in the enamel was determined. The concentration of F, Ca, P and insoluble extracellular polysaccharide (EPS) in the biofilm were analyzed. Results: The addition of CPP-ACP-TMP to 1100F reduced %SH by 42 % and 39 % when compared to the 1100F and 1100F-CPP-ACP (p < 0.001); in addition, to a reduction in lesion body (ΔKHN) by 36 % for the same treatments. The treatment with 1100F-CPP-ACP-TMP led to a significant increase in the concentration of F, P and Ca in the enamel and biofilm, and reduced the concentration of EPS (p < 0.001). Significance: Toothpaste formulation containing 1100F-CPP-ACP-TMP prevented the reduction of enamel hardness and significantly influenced the ionic biochemical composition and insoluble extracellular polysaccharide (EPS) in biofilm formed in situ. These results are promising and provide valuable insights for the design of further clinical trials.
Keywords: Biofilm; Demineralization; Dental enamel; Phosphates